MIDLIFE STRESSFUL OCCUPATIONAL EXPOSURES AND HIPPOCAMPAL SIZE IN HEALTHY OLDER ADULTS. (11th November 2018) - Jiao, Y; Ganster, D; Nicholson, R; O'Connor, D; McAuley, E; Kramer, A; Burzynska, A
Abstract: Raising retirement age warrants better understanding of the role of occupation in brain aging. Although occupational stress has been linked to decreased brain volumes in younger workers (Savic, 2015), the role of occupational stress in brain aging remains unknown. In order to address this relationship, we conducted two studies relating past occupational characteristics to MRI data from older adults. First, we assess occupational stress using the Work Design Questionnaire (Morgeson & Humphrey, 2006) combined with interpersonal conflict and workload questionnaires in 101 healthy adults (Mage=70, a subsample of NCT01472744 trial). We measured hippocampal volume with Magnetic Resonance Imaging. Greater physical demands of participants' most recent job were related to smaller left (F(4, 93)=10.5, p=.006, sr=-.260) and right hippocampi (F(4, 93)=7.18, p=.024, sr=-.231, both corrected for age, education, total brain volume). Greater physical demand was also associated with lower episodic memory scores (F(3, 97)=2.8, p=.006, sr=-.272, corrected for age and education). Next, we tested this finding in 83 cognitively healthy older adults (Mage=69), a subsample of an Acting Out trial (5R01AG036682-03). Here, we used these participants' primary midlife job titles and descriptions (Bureau of Labor Statistics, 2017) to categorize the participants into those with high (n=31) and low (n=52) occupational physical demands. Older adults whose midlife jobs were characterized by greater physical demands had smaller left (p=.019) and right (p=.035) hippocampi. Together, we identified occupational physical demands as stressful factor that may negatively impact brain aging. Future analyses should contrast the opposing effects of leisure physical activity and work physical demands on brain aging.